Polyacrylamide gels with selective recognition of the tetrameric molecular form of human growth hormone - Kublickas, R.; Werner, Carsten; Voit, Brigitte (eXPRESS Polymer Letters, 2017)
Networks of polyacrylamide were studied for the possibility of imprinting of the oligomeric form of human growth hormone. The tetrameric molecular form of human growth hormone was molecularly imprinted for the first time. The results show that approximately 50-70% (w/w) of the templates (depending on polymerization conditions) could be extracted from the molecularly imprinted acrylamide polymers. The resulting ‘gel antibodies’ against this form of human growth hormone in the form of granules of polyacrylamide were compared with granules of non-imprinted polymer. The selectivity of the artificial gel antibodies was studied. Investigation of the binding to imprinted polymer of the template hormone, other molecular forms of the hormone and other proteins shows the selectivity of the developed artificial gel antibodies.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Human growth hormone; Molecularly imprinted polymers; Polymer gels